Preoperative Classification System Used to Determine Release Performed during Endoscopic Brow Lift - Freeman, M. Sean (Facial Plastic Surgery, 2021)
The techniques presented in article will allow the facial plastic specialist to use the anatomy of each individual patient as a guide for the surgical release of the brow performed during endoscopic brow lift. The author presents his 15 years of experience in which he developed this approach. Five different surgical releases of the brow will be demonstrated and discussed in terms of which patients would best benefit from which release. Adopting this approach has made the predictability of the authors brow lift results much better and therefore improved patient satisfaction. This concept has not been described in the literature and the author firmly believes using a preoperative anatomical approach is a better way to approach endoscopic brow lift surgery.
Keywords: endoscopic brow lift; brow lift surgery; brow lift